PENGARUH CORPORATE SOCIAL RESPONSIBILITY DALAM PERSPEKTIF LINGKUNGAN TERHADAP MANAJEMEN LABA (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia 2012-2013) - Reza Hanung Pradipta; P. Basuki Hadiprajitno (Diponegoro Journal of Accounting, 2015)
This study aims to examine the effect of corporate social responsibility (CSR) in environmental perspective to earnings management. The purpose of this study is to provide empirically evidence about the effect of CSR in environmental perspective to earnings management. The independent variable of this study is CSR, the dependent variable is earnings management, and control variables are natural logarithm of firm size, leverage and profitability measured by return on asset (ROA). CSR measured by CSR disclosure with GRI G3.1, environmental disclosure as the indicator. Firm size measured by using natural logarithm of total assets. Leverage measured by comparing total debt with total assets. Profitability measured by using return on assets (ROA). ROA measured by comparing total net profit with total assets. Earnings management measured by discretionary accruals (DA). The population in this study are 298 manufacturing companies which listed on Indonesian Stock Exchange in the period of 2012-2013. Sample were selected by purposive sampling method and finally obtained 146 manufacturing companies that fulfill the criteria. Data were analyzed using multiple regression analysis model.The result show that CSR significant positively influence earnings management. Based on the result, it conclude that earnings management decision is influenced by its attitude about CSR.